Quality Analysis Of Room Natural Lighting Using Spatial Interpolation With Kriging Method - Soewono, Soetjipto; Febrina Rizal, Ayu (Devotion : Journal of Community Service, 2022)
The results of this study, where natural lighting can affect the lighting in the room, with the entry of natural lighting into the room through 4 open windows. The data retrieval process is for 1 day through special interpolation measurements using the Kirging method. The stages of data collection are in the morning, afternoon and evening with 3 windows open and 4 windows open. The intensity of light when 3 windows are open is a minimum average of -50 lux – 1350 lux in the morning and a maximum of -50 lux -1450 lux during the day, while the condition of 4 open windows is that the minimum average lighting is 0 – 1700 lux in the morning and maximum 50 lux -1750 lux during the day d. natural lighting can make reference to the lighting schedule in the room where the condition of 4 open windows is a mix of 5 points in the afternoon and a minimum of 3 points during the day. The electric power obtained is a maximum of 36 kWh, a minimum of 21.5 kWh and the resulting cost is a maximum of RP. 51,597, a minimum of RP. 30,814.87 so that the average energy efficiency of electric power reaches 11. 75%, the highest and the lowest reaches 11. 58% and efficiency towards costs reaches 58%.